2018
DOI: 10.1186/s12974-018-1208-3
|View full text |Cite
|
Sign up to set email alerts
|

Laquinimod protects the optic nerve and retina in an experimental autoimmune encephalomyelitis model

Abstract: BackgroundThe oral immunomodulatory agent laquinimod is currently evaluated for multiple sclerosis (MS) treatment. Phase II and III studies demonstrated a reduction of degenerative processes. In addition to anti-inflammatory effects, laquinimod might have neuroprotective properties, but its impact on the visual system, which is often affected by MS, is unknown. The aim of our study was to investigate potential protective effects of laquinimod on the optic nerve and retina in an experimental autoimmune encephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 75 publications
1
51
0
Order By: Relevance
“…This outcome might also be due to the nature of the MOG 35-55 EAE model, in which several studies aimed at RGC neuroprotection have indicated a huge variability in RGC survival from no to almost complete preservation. [40][41][42] An important factor on RGC survival in EAE models may be the timing of intervention and response of dosages, as nicely demonstrated by Wilmes et al 41 The group of Shindler et al reported a strong correlation on the magnitude RGC survival and the timepoint of corticosteroid intervention in the PLP-induced EAE model. 43 We used a single injection of MSC seven days after EAE induction and taking the half-life of MSC into consideration, a single MSC injection rather than multiple administrations might limit longer lasting neuroprotection as indicated by Payne et al 44 On the other hand, we see a robust rescue effect of the PERG amplitude, preservation of the RNFL, and notable mitigation of RGC loss, which is indicative of a sustained effect on the visual system.…”
Section: Discussionmentioning
confidence: 94%
“…This outcome might also be due to the nature of the MOG 35-55 EAE model, in which several studies aimed at RGC neuroprotection have indicated a huge variability in RGC survival from no to almost complete preservation. [40][41][42] An important factor on RGC survival in EAE models may be the timing of intervention and response of dosages, as nicely demonstrated by Wilmes et al 41 The group of Shindler et al reported a strong correlation on the magnitude RGC survival and the timepoint of corticosteroid intervention in the PLP-induced EAE model. 43 We used a single injection of MSC seven days after EAE induction and taking the half-life of MSC into consideration, a single MSC injection rather than multiple administrations might limit longer lasting neuroprotection as indicated by Payne et al 44 On the other hand, we see a robust rescue effect of the PERG amplitude, preservation of the RNFL, and notable mitigation of RGC loss, which is indicative of a sustained effect on the visual system.…”
Section: Discussionmentioning
confidence: 94%
“…However, while a subset of cone photoreceptors exhibited Cre-dependent tdTomato expression, no rod photoreceptors or bipolar cells expressed Cre in Vglut2-Cre;ndufs4 loxP/loxP mice and would therefore be expected to be physiologically normal. It is conceivable that a mild reduction in b-wave amplitudes could be an indirect effect of RGC pathology and/or inner retinal inflammation, as animal models of traumatic or inflammatory optic neuropathy have exhibited variable effects on outer retinal signaling properties 34,35 . The reduction in oscillatory potentials observed in ERG recordings of the conditional knockout mice is consistent with abnormal RGC function, as seen previously in mouse glaucoma models 33,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in AhR-knockout mice, no effect of LQ on the number of IBA1-positive cells was found [262], indicating that AhR is the main target of LQ. LQ also decreased the number of MAC-3-and CD45-positive microglia cells in cuprizone mice, EAE mice and mouse TLR4-knockout and myeloid differentiation primary response 88 (MyD88)-knockout demyelination models [261,[265][266][267][268][269]. Moreover, LQ increased the protein level of the pro-inflammatory microglia marker translocator protein (TSPO) [267] in the CNS of cuprizone-exposed mice [265].…”
Section: Microgliamentioning
confidence: 93%
“…LQ is an orally administered, synthetic derivative of linomide, that targets peripheral immune cells, such as activated IL-21-producing CD4 + CD44 + T-cells, C11c + CD4 + dendritic cells dendritic cells and B-cells [260], but it also displays neuroprotective effects in the mouse EAE model [30,31]. In addition, the linomide derivative might work via the AhR because LQ-treated mice showed major transcriptional changes of genes downstream of this receptor [261], such as the AhR hydroxylase Cytochrome P450 (CYP1A1). Here, we deal with the specific molecular effects of LQ on CNS cell types (for details, see Supplementary Table S6; for article search terms, see Supplementary Information).…”
Section: Molecular Effects Of Lqmentioning
confidence: 99%